Prevalence of canine parvo virus and canine influenza virus infection in dogs in Dhaka, Mymensingh, Feni and Chittagong districts of Bangladesh - Sen, Soumitra; Rahman, Md Siddiqur; Nag, Minakshi; Rahman, Mohummad Muklesur; Sarker, Roma Rani; Kabir, S M Lutful (Asian Journal of Medical and Biological Research, 2016)
<!--[if gte mso 9]> ismail - [2010] 11.5606 <![endif]--> Canine parvovirus (CPV) and canine influenza virus (CIV) are highly contagious virus infecting members of the canine family including dogs, coyotes, foxes and wolves. The research work was carried out to determine the prevalence of CPV and CIV in dogs (stray and pet dogs) in Dhaka, Mymensingh, Feni and Chittagong Districts by using Rapigen CPV and CIV Ag test kit. Fecal samples were collected from 50 dogs of different age and sex from different spots of Dhaka and Chittagong District. Nasal fluid samples were collected from 50 dogs of different age and sex from different spots. The samples were tested with Rapigen canine parvovirus Ag test kit and Rapigen canine influenza Ag test kit. Overall prevalence of CPV in pet dogs was 22% and in stray dogs was 30%. The prevalence of canine parvovirus in relation to age was gradually decreasing with higher age group and the prevalence was 28% in 1-6 months age, 16.66% in 7-12 months age group 11.11%o ver 18 months age group. The prevalence of canine parvovirus was significantly higher in male (24.13%) than that in female (19.04%). All samples showed negative test result for canine influenza virus. Prevalence of canine influenza virus infection were 00.00% in all age groups and sex. Overall prevalence of CIV in all pet and stray dogs were 00.00%. Asian J. Med. Biol. Res. March 2016, 2(1): 138-142 <!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]-->